2018
DOI: 10.1038/s41374-018-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of E-cadherin by PPBICA protects against cisplatin-induced acute kidney injury by attenuating inflammation and programmed cell death

Abstract: E-cadherin is a major component of tubular adherent proteins that maintain intercellular contacts and cell polarity in epithelial tissue. It is involved in pathological processes of renal cell carcinoma and fibrotic diseases via epithelial-mesenchymal transition. Although studies have shown E-cadherin is significantly downregulated in acute kidney injury (AKI), its function in AKI is unknown. Here, we evaluated cell damage and inflammation in cisplatin-stimulated tubular epithelial cell lines after disrupting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…E-cadherin, ZO-1, and Claudin-2 whilst upregulating those more commonly associated with a mesenchymal phenotype and increased fibrosis, e.g. α-SMA, Ncadherin, and Snail [32][33][34]. Initiation is associated with disassembly and breakdown of adherens junctions and tight junctions, culminating in loss of cell adhesion and increased paracellular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin, ZO-1, and Claudin-2 whilst upregulating those more commonly associated with a mesenchymal phenotype and increased fibrosis, e.g. α-SMA, Ncadherin, and Snail [32][33][34]. Initiation is associated with disassembly and breakdown of adherens junctions and tight junctions, culminating in loss of cell adhesion and increased paracellular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of E-cadherin (ECAD) mediated cell-cell adhesion is pivotal in initiating a series of phenotypic and morphological events that precede tubulointerstitial fibrosis [27,32,33], with the disassembly of the adherens junction (AJ) and tight junction (TJ) complexes linked to loss of epithelial stability, inflammation, fibrosis and impaired renal function [34,35]. In the present study, we combine in vivo and in vitro models of CKD to investigate if targeting Cx43 expression and hemichannel activity through genetic and pharmacological blockade, could negate loss of markers linked with tubular injury, ultimately improving function through diminished hemichannel activity, restoration of E-cadherin mediated cell-cell adhesion and reduced paracellular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The means by which a soluble protease reaches the glomerulus requires further study but could theoretically occur through several pathways, including diffusion from nearby tubules. Further, it is well known that tubular injury can lead to tubular apoptosis, loss of barrier integrity, and the potential backleak of substances through injured tubules, which could affect glomeruli (31)(32)(33)(34). Finally, it is possible that MMP-7 enters the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic pathways in the tubular epithelium could be induced by caspase cascade activation, mitochondrial injury, ER stress, etc. Apoptosis also promoted the loss of renal epithelial cells that characterized AKI [11,34,35]. Accumulating evidences demonstrated that the activation of caspase 3 was predominant which responsible for renal tubular cell apoptosis in cisplatin-induced AKI [13,36].…”
Section: Discussionmentioning
confidence: 99%